2011
DOI: 10.1186/1471-2164-12-623
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenism in social insects: insights from a transcriptome-wide analysis of gene expression in the life stages of the key pollinator, Bombus terrestris

Abstract: BackgroundUnderstanding polyphenism, the ability of a single genome to express multiple morphologically and behaviourally distinct phenotypes, is an important goal for evolutionary and developmental biology. Polyphenism has been key to the evolution of the Hymenoptera, and particularly the social Hymenoptera where the genome of a single species regulates distinct larval stages, sexual dimorphism and physical castes within the female sex. Transcriptomic analyses of social Hymenoptera will therefore provide uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 87 publications
11
72
0
Order By: Relevance
“…In bumblebees, the presence of queen diapause has been proposed to be a prerequisite for the evolution of sociality by co-option of the diapause-regulating gene network for new roles in caste differentiation (Hunt and Amdam, 2005; Hunt et al, 2007). Several studies have investigated the genetics underlying diapause in bumblebees (Kim et al, 2006, 2008; Colgan et al, 2011), including a very recent study communicating a genome-wide transcriptome comparison targeting the fat body of diapausing Bombus terrestris queens (Amsalem et al, 2015b). The latter study, concurrent with our own investigations, highlighted the functional association of the genes highly expressed in the queen's fat body with nutrient storage and stress resistance, as well as a different role of JH and Vg in diapausing bumblebee queens when compared to dipteran models.…”
Section: Introductionmentioning
confidence: 99%
“…In bumblebees, the presence of queen diapause has been proposed to be a prerequisite for the evolution of sociality by co-option of the diapause-regulating gene network for new roles in caste differentiation (Hunt and Amdam, 2005; Hunt et al, 2007). Several studies have investigated the genetics underlying diapause in bumblebees (Kim et al, 2006, 2008; Colgan et al, 2011), including a very recent study communicating a genome-wide transcriptome comparison targeting the fat body of diapausing Bombus terrestris queens (Amsalem et al, 2015b). The latter study, concurrent with our own investigations, highlighted the functional association of the genes highly expressed in the queen's fat body with nutrient storage and stress resistance, as well as a different role of JH and Vg in diapausing bumblebee queens when compared to dipteran models.…”
Section: Introductionmentioning
confidence: 99%
“…Quality analyses of the transcripts indicate that the assembly is comparable to other bee transcriptomes (Colgan et al 2011;Kocher et al 2013;Rehan et al 2014;Harrison et al 2015) and has a high sequencing coverage (about 150 x per transcriptome). In both life cycle stages, more than 60% (60.9% in adult females and 66.2% in larvae) of the transcripts had a significant blast hit against a sequence in the UniRef database, especially against bees and other Hymenoptera sequences (Online Resource 3).…”
Section: Discussionmentioning
confidence: 91%
“…Functional genomic techniques, such as RNA‐Seq, provide an unbiased view into genome‐wide transcriptional changes and have been applied to microparasite–insect systems to elucidate genes underlying complex altered host phenotypes (Choi et al ., ; Geffre et al ., ). For the bumblebee, recent developments in genomics and transcriptomics have provided the tools to explore important aspects of host biology, including phenotypic polymorphism (Colgan et al ., ; Harrison et al ., ), caste differentiation (Collins et al ., ; Woodard et al ., ), mating success (Manfredini et al ., ) and diapause regulation (Amsalem et al ., ). In relation to pathogen response, previous transcriptomic studies have identified changes in host immune expression in response to the trypanosomatid Crithidia bombi (Barribeau et al ., ) and bacterial challenge (Barribeau et al ., ).…”
Section: Introductionmentioning
confidence: 99%